2003
DOI: 10.1245/aso.2003.03.061
|View full text |Cite
|
Sign up to set email alerts
|

Superior Survival in Treatment of Primary Nonmetastatic Pediatric Osteosarcoma of the Extremity

Abstract: This study demonstrates excellent survival with a dose-intensified neoadjuvant protocol. Future endeavors should involve a multi-institutional randomized study comparing this approach with another multiagent intravenous neoadjuvant protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(40 citation statements)
references
References 31 publications
1
39
0
Order By: Relevance
“…Recent studies have demonstrated a more favorable outcome, especially for patients with nonmetastatic osteosarcoma 5, 6. Five‐year survival rates of 60% to 80% have been reported for patients receiving intensive multidrug chemotherapy and surgery for aggressive local control 5, 6, 7, 8, 9, 10, 11. However, despite the recent improvement in survival, a substantial number of patients still develop metastases or suffer tumor‐related death, so more accurate identification of patient subgroups with different levels of risk is substantially important.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated a more favorable outcome, especially for patients with nonmetastatic osteosarcoma 5, 6. Five‐year survival rates of 60% to 80% have been reported for patients receiving intensive multidrug chemotherapy and surgery for aggressive local control 5, 6, 7, 8, 9, 10, 11. However, despite the recent improvement in survival, a substantial number of patients still develop metastases or suffer tumor‐related death, so more accurate identification of patient subgroups with different levels of risk is substantially important.…”
Section: Introductionmentioning
confidence: 99%
“…50 Although data focusing on the spine are scant, it is notable that the addition of chemotherapy to wide surgical excision in appendicular osteosarcoma has greatly increased survival. 36,37,39,40,42,49,51,55,64 Importantly, a large study by Link et al demonstrated that patients undergoing surgery only had a 2-year relapse-free survival rate of 17% versus 66% in the adjuvant chemotherapy group among 36 randomized patients, which was further supported by similar results in 77 patients who refused randomization. 37 Gherlinzoni et al further found that the incidence of local recurrence was related above all to adjuvant chemotherapy-induced tumor necrosis.…”
Section: Discussionmentioning
confidence: 87%
“…17 The highest response rate (approximately 81%) was reported for the most part in a pediatric population. 18 Chemotherapy-related toxicities in previous studies have been reported as Grade 3-4 nausea and emesis and myelosuppression and the majority subside with supportive therapy. 14,15 The toxicities reported in the T10, T12, COSS-80, COSS-82, and OS-2 protocols are similar, with myelotoxicity being the most commonly reported toxicity.…”
Section: Discussionmentioning
confidence: 98%